Finding, Excursion and Museum: William Henry Hudson’s Birthplace Transformations in El Hornero Journal - Maranguello, Carolina (2023)
Within the framework of the Argentinian reception of the work of writer and naturalist William Henry Hudson, read from aesthetically and ideologically divergent sectors, this paper investigates the early recovery of his figure in the ornithological journal El hornero. As it will be seen, one of the ways of reinserting him as a “national” naturalist and universal writer is produced from the patrimonial discovery and restoration of his affective topography, particularly his mythical birthplace in Los veinticinco ombúes ranch. The management and visibility operations carried out by El hornero do not take place on the native space as a crystallized territory, but rather on the temporary transformations that it experiences: the house where he was born is, first of all, a ruin that could be identified thanks to Hudson’s formidable “topographical memory” and the efforts of his main promoter, Fernando Pozzo; then, the house becomes a destination for scientific excursions and, finally, a house-museum project. Each of these forms by which Hudson's home and biography are declined at the same time condenses the journal's scientific, literary and patrimonial interests, and offers different forms of collaboration and dispute between national and foreign political and scientific figures.